2021
DOI: 10.13075/ijomeh.1896.01649
|View full text |Cite
|
Sign up to set email alerts
|

Formalin safety in anatomic pathology workflow and integrated air monitoring systems for the formaldehyde occupational exposure assessment

Abstract: The potential carcinogenicity of formaldehyde (FA) has prompted increasing preventive measures in anatomic pathology (AP) laboratories and new strategies aimed at innovating airborne FA monitoring systems. This review provides an updated overview of the most recent improvements in preventive measures, safe practices, and exposure monitoring tools in the FA usage and handling. A computer-based search of scientific and non-scientific sources was performed on PubMed, Web of Science, Google and Google Patents data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This percentage raised up to 88.8-98.1% when the improvement of the ventilation system was combined with a training program to educate local workers and with the use of a negative pressure room (d 'Ettorre et al 2021). Good results were also obtained when the enhancement of the ventilation system was coupled with the use of a vacuum sealing machine and a fume hood computer-based system (Dugheri et al 2020; reduction percentage: 78-95.4%). Ogawa et al (2019) reported a lower reduction percentage (56.7%) when the improvement of the ventilation system was combined with workers' training and the use of a video camera and a volatile organic compound detector (Ogawa et al 2019).…”
Section: Main Characteristics Of the Studies Performed In Healthcare ...mentioning
confidence: 99%
“…This percentage raised up to 88.8-98.1% when the improvement of the ventilation system was combined with a training program to educate local workers and with the use of a negative pressure room (d 'Ettorre et al 2021). Good results were also obtained when the enhancement of the ventilation system was coupled with the use of a vacuum sealing machine and a fume hood computer-based system (Dugheri et al 2020; reduction percentage: 78-95.4%). Ogawa et al (2019) reported a lower reduction percentage (56.7%) when the improvement of the ventilation system was combined with workers' training and the use of a video camera and a volatile organic compound detector (Ogawa et al 2019).…”
Section: Main Characteristics Of the Studies Performed In Healthcare ...mentioning
confidence: 99%
“…Currently, although there are alternative methods to the use of FA, such as the practice of Under-Vacuum Sealing (UVS) (Bellisario et al 2016 ), FA is still considered the standard fixative for routine work. In Italy, 1726 workers employed in specialised hospital activities had been estimated to be potentially exposed to FA (Scarselli et al 2017 ; Dugheri et al 2021 ). To safeguard workers occupationally exposed to air-FA, various limits of exposure have been proposed, even though there is no agreement between the international agencies (Dugheri et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, 1726 workers employed in specialised hospital activities had been estimated to be potentially exposed to FA (Scarselli et al 2017 ; Dugheri et al 2021 ). To safeguard workers occupationally exposed to air-FA, various limits of exposure have been proposed, even though there is no agreement between the international agencies (Dugheri et al 2020 ). The current Threshold Limit Value—Time Weighted Average (TLV – TWA) recommended by the American Conference of Governmental Industrial Hygienists (ACGIH) is 120 μg/m 3 (i.e., 0.1 ppm) and is referred to average exposure in eight-hour workdays (Dugheri et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Formaldehyde (FA) is globally synthesized on a large scale by catalytic oxidation of methanol in the vapor phase [ 1 ]. FA is commonly used to produce industrial chemicals [ 2 , 3 , 4 ], and its aqueous solution (known as formalin) has many applications as a sanitizer and preservative [ 5 ].…”
Section: Introductionmentioning
confidence: 99%